2016
DOI: 10.1038/srep34433
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment of microRNA-188-5p restores the synaptic and cognitive deficits in 5XFAD Mouse Model of Alzheimer’s Disease

Abstract: MicroRNAs have emerged as key factors in development, neurogenesis and synaptic functions in the central nervous system. In the present study, we investigated a pathophysiological significance of microRNA-188-5p (miR-188-5p) in Alzheimer's disease (AD). We found that oligomeric Aβ 1-42 treatment diminished miR-188-5p expression in primary hippocampal neuron cultures and that miR-188-5p rescued the Aβ 1-42 -mediated synapse elimination and synaptic dysfunctions. Moreover, the impairments in cognitive function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…The recovery of cognitive function can be achieved by restoring the reduced microRNAs acting at the synaptic level. The abnormal down-regulation of miR-188-5p is reported in the cerebral cortices and hippocampus of AD patients when compared with age-matched control subjects (42). Dendritic spine and synapse loss are welldocumented in AD.…”
Section: Microrna-mediated Synaptic Dysfunction In Admentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery of cognitive function can be achieved by restoring the reduced microRNAs acting at the synaptic level. The abnormal down-regulation of miR-188-5p is reported in the cerebral cortices and hippocampus of AD patients when compared with age-matched control subjects (42). Dendritic spine and synapse loss are welldocumented in AD.…”
Section: Microrna-mediated Synaptic Dysfunction In Admentioning
confidence: 99%
“…Long-term potentiation (LTP) is believed to be a synaptic mechanism underlying the storage of long-term memory in the brain. The replenishment of miR-188-5p can improve behavioral outcomes and enhance synaptic activity, importantly, and restore cognitive function in AD mouse models such as 5XFAD mice (42,43). However, some microRNAs are abnormally elevated in AD models and could have negative effects on neurons.…”
Section: Microrna-mediated Synaptic Dysfunction In Admentioning
confidence: 99%
“…However, it is still not clear whether undefined miRs that target BACE1 contribute to the development of AD neuropathology. In particular, only a few studies have been conducted to determine whether a reversal of miR(s) targeting BACE1 alleviates AD neuropathology in vivo (23,25,26). Our previous study demonstrated that overexpression of miR-188-3p, which also targets BACE1, ameliorates neuropathology and improves synaptic function in 5XFAD TG mice (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several miRs that target BACE1, a key enzyme responsible for Ab formation (20)(21)(22)(23)(24), but only a few studies have been conducted to determine whether restoration or reversal of dysregulated miRs targeting BACE1 is capable of reducing Ab production, which in turn, alleviates neuropathology of AD (23,25,26). In our previous miR microarray screening, we identified several deregulated miRs in the hippocampus of 5XFAD transgenic (TG) mice, a mouse model of AD (25).…”
mentioning
confidence: 99%
“…Plenty of studies have pointed to the involvement of miRNAs in various diseases, including cancer, (3)(4)(5)(6) heart diseases, (7,8) lung diseases, (9,10) nervous system disorders, (11,12) and even genetic diseases. (13)(14)(15) MicroRNAs can be transported in the extracellular circulation in several ways, including: (1) complexed with highdensity lipoproteins (HDL) or the Ago2 protein; (16) (2) encapsulated within microvesicles; (17) (3) accumulated in apoptotic bodies; (18) and (4) packaged within exosomes.…”
Section: Introductionmentioning
confidence: 99%